How the Halakhah Unfolds: Hullin in the Mishnah, Tosefta, and Bavli, Part One: Mishnah, Tosefta, and Bavli - Zahavy, Tzvee; Neusner, Jacob (Hamilton Books, 2010)
In separate multi-volume works, the project has presented form-analytical English translations of the Mishnah, Tosefta, Yerushalmi, and Bavli, outlined the Yerushalmi and the Bavli and compared these outlines. In this volume, the main points of the Halakhah of the topological expositions or tractates of the Mishnah-Tosefta-Bavli Hullin are set forth and the theological message of the tractate is laid out. The project yields a systematic account of the Halakhah in its documentary unfolding.